Syurga Shawl Enterprise / Jubaidah Mohd Salleh ... [et al.] - Mohd Salleh, Jubaidah; Kamsul, Natasyah; Amir, Siti Hajar; Abtar, Ahmad Subree; Adilun, Mohamad Mahadi (2012)
Our target for those students in UITM who will interest in our business. We are providing with several of shawls and accessories. Other than that, we will include extra product which is accessories and consultation service to our customer. Variety of goods as planned in this business can facilitate students to acquire their needs and they do not have to go to the city. Consultation services that would be provided to the students also can contributes to our business popularity indirectly. A business plan is a written document that serves as a guide and blueprint for a proposed business project that one intends to undertake. The information gathered regarding the project used in the business plan to predict viability, forecast success and propose strategies for the project.